Influência do tamanho das partículas do fosfato de Araxá sobre a produção de matéria seca do sorgo - Quintâo Lana, Regina Maria; Braga, José Mário; Ribeiro, Antônio Carlos; L Thiébaut, José Tarcísio; Lima Neves, Júlio César (Revista Ceres, 2025)
Experiments were carried out in pots, in the greenhouse, to evaluate the effects of particle size of Araxa phosphate rock (0-10; 10-20; 20-48; 48-100; 100-150; 150-200; 200-270 and larger than 400 mesh/inch), phosphorus sources (Araxa phosphate rock and triple superphosphate), phosphorus levels (25% and 75% of the maximum soil adsorption capacity), and liming (presence and absence) on dry matter production of two sorghum hybrids (CMSXS 136 and CMSXS 903, tolerant and sensitive to aluminum, respectively). The hybrids were seeded and harvested in the same pots three times, consecutively. At each time, the plants wereharvested 40 days after emergence and separated as to shoot and root, then dried and weighed.